A causal model of external marketing research information utilization in British companies - Kortam, Wael Abdelrazek (1997)
The main objectives of this research are to enhance the academic understanding and managerial practice of the utilization of external marketing research information with special reference to British companies. To achieve these objectives, this thesis proposes a causal model of external marketing research information utilization and tests its hypotheses empirically in British industry. This model builds on and develops existing theoretical and empirical work. The research evolved through three major phases. The first phase of the research was conceptual concerned with demonstrating the practical and theoretical importance of researching the topic of utilization, determining the appropriate perspective to studying it and establishing a valid and reliable framework for its definition and measurement. This part has relied on review of the literature on utilization of information in marketing and other management areas along with available secondary data about the UK market research industry as the institutional context of this research.